P3.446 Excellent Efficacy of PRITELIVIR (AIC316) in Suppression of Genital Herpes, a Novel Drug Against Herpes Simplex Virus (HSV) Type 1 and 2. (13th July 2013) - Birkmann, A; McCormick, D; Kropeit, D; Timmler, B; Stoelben, S; Wald, A; Field, H; Richard, M P; Zimmermann, H; Rübsamen-Schaeff, H
Abstract : Genital Herpes is generally being caused by HSV-2, although genital infections with the "labial" herpes virus, HSV-1, have been increasing. Transmission of the herpes virus has become a major health concern since it also promotes transmission of other sexually transmitted diseases, e.g. HIV. Nucleoside analogues are widely used for treatment of genital herpes, but recurrences still occur after cessation of therapy and even under long-term treatment. Furthermore, genital transmission of HSV-2 cannot efficiently be prevented by existing drugs. PRITELIVIR (AIC316) belongs to a novel class of antiviral compounds with activity against HSV-1 and HSV-2. In contrast to nucleoside analogues targeting the viral DNA polymerase PRITELIVIR (AIC316) prevents the de novo synthesis of viral DNA through inhibition of the viral helicase-primase complex. PRITELIVIR (AIC316) therefore does not require activation by the viral thymidine kinase and is protective for uninfected cells. In vitro and in vivo, PRITELIVIR (AIC316) exhibited potent and rapid antiviral activity as well as superior efficacy against both HSV-1 and –2 compared to nucleoside analogues. In single and multiple dose phase I trials PRITELIVIR (AIC316) was safe with favourable pharmacokinetics resulting in a long half-life, indicative of efficacy with once per day dosing. In a recently completed phase II proof-of-concept and dose finding trial in subjects with genital herpes PRITELIVIR (AIC316) met the primary and secondary endpoint of the trial demonstrating excellent activity in reducing viral shedding in a dose dependent way and suppression of clinical symptoms, even with once weekly dosing. A head-to-head comparison trial with Valtrex is underway. In conclusion, PRITELIVIR (AIC316) represents a highly active and novel treatment option for HSV-1 and –2 infections with very convenient dosing.